Model validation and uncertainty quantification. proceedings of the 36th IMAC, a conference and exposition on structural dynamics 2018 /: proceedings of the 36th IMAC, a conference and exposition on structural dynamics 2018. Volume 3 : ([2019]) - Unknown
No abstract available